Developmental changes in neural stem cell expression in the spinal cord and the influence of painful stimulation - Edwards, Adele Georgina Amanda (2021)
Background and Aims: Neural stem cells (NSCs) are progenitors that play a fundamental role in the generation of glial cells and neurons in the developing central nervous system, but also remain in specific neurogenic regions in adulthood including the central canal of the spinal cord. NSCs have been explored in the spinal cord following adult spinal cord injury (SCI) but not in response to pain, and there is little understanding of NSC regulation in the spinal cord during postnatal development. The aims were to investigate NSC expression in the mouse spinal cord during different stages of postnatal development and determine whether there are changes in NSC marker distribution in the spinal cord following painful stimulation during early life. Methods: The expression of NSC markers Sox1 and Sox2 was assessed by immunohistochemical analysis in the spinal cord from transgenic Sox1-GFP and wild-type mice during different stages of postnatal maturation (postnatal day (P) 7-40). The potential effects of painful stimuli on NSC marker distribution in the spinal cord was studied using inflammatory (carrageenan) and neuropathic (cisplatin) pain models. In the carrageenan model, mice received an intraplantar injection of carrageenan or vehicle (saline) into the left hindpaw at P7 (0.5% carrageenan) or P14 (1% carrageenan). Nociceptive behavioural testing (von Frey testing) was performed at 4 hours, 24 hours, 48 hours, 72 hours, 96 hours and 120 hours following injection. The expression of NSC markers (Sox1 and Sox2) in the neonatal spinal cord following the carrageenan model was assessed by immunohistochemistry. The cisplatin model was induced at P14, mice received 1 mg/kg of cisplatin or vehicle (saline) subcutaneously for five consecutive days and von Frey testing was performed up to 35 days post-model induction. The expression of markers for glial cells (GFAP and Iba1), primary afferent fibres (CGRP and IB4) and NSCs was investigated in the spinal cord of adult mice that had received cisplatin during early life by immunohistochemistry. Results: GFP, Sox1 and Sox2 expression was observed around the central canal at all time points, but was also detected in other areas of the spinal cord including the superficial dorsal horn and directly lateral to the central canal. Expression in the superficial dorsal horn and directly lateral to the central canal was higher at P7 than at the later time points, although this was not statistically significant, indicating that NSC expression remained stable over the period considered. An intraplantar injection of carrageenan into the left hindpaw of P7 and P14 mice caused hyperalgesia at 4 hours post-injection that resolved by 120 hours with no significant differences in Sox1 and Sox2 expression observed. Analogous studies with the cytotoxic anti-cancer drug cisplatin produced delayed hyperalgesia in neonatal mice at 14 days post-model induction (onset P32) that persisted into adulthood (P53) compared to controls. There were also no significant differences in Sox1, Sox2, Iba1, GFAP, CGRP and IB4 expression. Conclusions: NSC marker expression in the spinal cord was investigated throughout postnatal development in mice and no significant changes were observed. This understanding is useful for the investigation of potential changes to NSCs in the spinal cord following different types of stimulation over the postnatal period. Although NSCs are activated in response to SCI, no significant changes in NSC marker expression were observed in the spinal cord following an acute inflammatory stimulus (carrageenan) or during a chronic neuropathic pain state (cisplatin) induced during early life. Although a behavioural response was observed, the cisplatin injected mice only had mild hyperalgesia, indicating that a higher dose of cisplatin may be required to induce a greater degree of hyperalgesia and assess whether this is linked to changes in NSC distribution.